Assessment of Water Distribution Network Skeletonization Using the Resilience Concept - Dhivakar, M.; Karthik, V. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The design of water distribution network is a combinatorial problem, which permits the heuristic and meta-heuristic algorithm to explore the solution in less computational time. The present study deals with proposing a model for the expansion work of an existing water distribution network of Bodinayakanur Municipality in Tamil Nadu State. In the proposed model EPANET is used for the hydraulic analysis and GA is used for the optimization of the water distribution network. The concept of resilience is used to generate skeletonized models of Water Distribution Networks (WDN). The network is skeletonized by removing from it those pipes with the minimum impact on the Resilience Index, assuring that all consumption nodes are still connected. The proposed methodology was applied to the case study WDN and the results obtained are satisfactory: the skeletonized models are able to reproduce the hydraulic behavior of the entire WDN with high accuracy.